Impact of blood flow on diffusion coefficients of the human kidney: A time‐resolved ECG‐triggered diffusion‐tensor imaging (DTI) study at 3T. Issue 1 (13th July 2012) - Heusch, Philipp; Wittsack, Hans‐Jörg; Kröpil, Patric; Blondin, Dirk; Quentin, Michael; Klasen, Janina; Pentang, Gael; Antoch, Gerald; Lanzman, Rotem S.
Abstract Purpose: To evaluate the impact of renal blood flow on apparent diffusion coefficients (ADC) and fractional anisotropy (FA) using time‐resolved electrocardiogram (ECG)‐triggered diffusion‐tensor imaging (DTI) of the human kidneys. Materials and Methods: DTI was performed in eight healthy volunteers (mean age 29.1 ± 3.2) using a single slice coronal echoplanar imaging (EPI) sequence (3 b‐values: 0, 50, and 300 s/mm2) at the timepoint of minimum (20 msec after R wave) and maximum renal blood flow (200 msec after R wave) at 3T. Following 2D motion correction, region of interest (ROI)‐based analysis of cortical and medullary ADC‐ and FA‐values was performed. Results: ADC‐values of the renal cortex at maximum blood flow (2.6 ± 0.19 × 10−3 mm2/s) were significantly higher than at minimum blood flow (2.2 ± 0.11 × 10−3 mm2/s) (P < 0.001), while medullary ADC‐values did not differ significantly (maximum blood flow: 2.2 ± 0.18 × 10−3 mm2/s; minimum blood flow: 2.15 ± 0.14 × 10−3 mm2/s). FA‐values of the renal medulla were significantly greater at maximal blood (0.53 ± 0.05) than at minimal blood flow (0.47 ± 0.05) (P < 0.01). In contrast, cortical FA‐values were comparable at different timepoints of the cardiac cycle. Conclusion: ADC‐values in the renal cortex as well as FA‐values in the renal medulla are influenced by renal blood flow. This impact has to be considered when interpreting renal ADC‐ and FA‐values. J. Magn. Reson. Imaging 2013;37:233–236. © 2012 Wiley Periodicals, Inc.